Unifying heterogeneous and distributed information about marine species through the top level ontology MarineTLO. Issue 1 (1st February 2016) - Tzitzikas, Yannis; Allocca, Carlo; Bekiari, Chryssoula; Marketakis, Yannis; Fafalios, Pavlos; Doerr, Martin; Minadakis, Nikos; Patkos, Theodore; Candela, Leonardo
Abstract : Purpose: – Marine species data are scattered across a series of heterogeneous repositories and information systems. There is no repository that can claim to have all marine species data. Moreover, information on marine species are made available through different formats and protocols. The purpose of this paper is to provide models and methods that allow integrating such information either for publishing it, browsing it or querying it. Aiming at providing a valid and reliable knowledge ground for enabling semantic interoperability of marine species data, in this paper the authors motivate a top level ontology, called MarineTLO and discuss its use for creating MarineTLO-based warehouses. Design/methodology/approach: – In this paper the authors introduce a set of motivating scenarios that highlight the need of having a top level ontology. Afterwards the authors describe the main data sources (Fisheries Linked Open Data, ECOSCOPE, WoRMS, FishBase and DBpedia) that will be used as a basis for constructing the MarineTLO. Findings: – The paper discusses about the exploitation of MarineTLO for the construction of a warehouse. Furthermore a series of uses of the MarineTLO-based warehouse is being reported. Originality/value: – In this paper the authors described the design of a top level ontology for the marine domain able to satisfy the need for maintaining integrated sets of facts about marine species and thus assisting ongoing research on biodiversity. Apart from the ontology the authors also elaborated with the mappings that are required for building integrated warehouses.